Answer:
10t - 16
Step-by-step explanation:
4(t + 2)+ 6(t - 4)
4t + 8 + 6t -24
10t - 16
<span>3x+4=y+5, then y+5=3x+4
It is called: reflexive property
-----------------------------
</span>
<span>x = y and y = 10, then x = 10
It is called: equality substitution property
</span>
Answer:
x = 3
Step-by-step explanation:
7/x - 3/(2x) + 7/6 = 9/x
x(7/x - 3/(2x) + 7/6) = x(9x)
x*7/x - 3*x/(2x) + x*7/6 = x*9x
7 - 3/2 + 7x/6 = 9
7x/6 = 9 - 7 + 3/2
7x/6 = 2 + 3/2
7x/6 = 12/6 + 9/6
7x = 12+9
7x = 21
x = 21/7
x = 3
probe:
7/3 - 3/(2*3) + 7/6 = 9/3
14/6 - 3/6 + 7/6 = 3
(14 - 3 + 7) / 6 = 3
18/6 = 3
Answer:
3848,451001
Step-by-step explanation:
A = πr²
A = π[35]²
A = 1225π
A = 3848,451001
I hope this is correct, and as always, I am joyous to assist anyone at any time.